Spontaneous Rupture of Renal Cell Carcinoma in Pregnancy: A Case Report - Mohamed Zakieldahshoury; Hassaan A. Gad; Salah Ahmed (Gynecology Obstetrics & Reproductive Medicine)
Renal cell carcinoma is the most common type of malignancy in pregnancy. Rupture of renal cell carcinoma is not uncommon. The diagnosis of renal cell carcinoma is often delayed as the clinical presentation might resemble other pregnancy-related disorders or asymptomatic in most cases and a complete ultrasonographic examination of the abdomen is not a part of the routine obstetric evaluation. We report a rare case with spontaneous rupture of renal cell carcinoma in 20 years old in full-term pregnancy primigravida presented by hypertensive disorder and severe abdominal pain with massive retro peritoneum collection, radical nephrectomy was done and the patient life was saved.